Advanced computational intelligence paradigms in healthcare 6. virtual reality in psychotherapy, rehabilitation, and assessment - Brahnam, Sheryl; Jain, Lakhmi C. (Studies in computational intelligence, 2011)
This volume presents the latest research in Virtual Reality (VR), as it is being applied in psychotherapy, rehabilitation, and the analysis of behaviour for neurological assessment. This book will be of value to anyone already in the field and to those who are interested in the development of VR systems for therapeutic purposes. The contents include: The latest literature reviews on VR in psychotherapy, psychological wellbeing, and rehabilitation; VR and cognitive behavior therapy; Increasing presence in VR for effective exposure therapy and treatment of anxiety disorders; VR military training for managing combat stress and preventing post traumatic stress; VR, mixed reality systems, and games for stroke rehabilitation; VR systems for improving vision in children with amblyopia; Therapeutic play in virtual environments; Healing potential of online virtual worlds such as Second Life; Neuropsychological assessment using virtual environments; Detailed accounts on how VR systems are designed, implemented, and best evaluated; Discussions of limitations, problems, and ethical concerns using VR in mental and physical therapy.